A Novel Role for α-Importins and Akirin in Establishment of Meiotic Sister Chromatid Cohesion in Caenorhabditis elegans. Issue 2 (18th December 2018) - Bowman, Richard; Balukoff, Nathan; Ford, Talitha; Smolikove, Sarit
Abstract: During meiotic prophase I, sister chromatid cohesion is established in a way that supports the assembly of the synaptonemal complex (SC). The SC connects homologous chromosomes, directing meiotic recombination to create crossovers. In this paper, we identify two proteins that cooperate to import and load meiotic cohesins, thus indirectly promoting SC assembly. AKIR-1 is a protein with a previously identified meiotic role in SC disassembly. akir-1 mutants have no obvious defects in sister chromatid cohesion. We identified ima-2, a gene encoding for an α-importin nuclear transport protein, as a gene interacting with akir-1 . Analysis of akir-1 ;ima-2 double mutants reveals a decrease in the number of germline nuclei and the formation of polycomplexes (PCs) (an SC protein aggregate). These PCs contain proteins that are part of the two main substructures of the SC: the central region and the lateral element. Unlike typical PCs, they also contain sister chromatid cohesion proteins. In akir-1 ;ima-2 double mutants, PCs are located in both the nucleus and the cytoplasm. This suggests that the defects observed in the double mutants are both in nuclear import and in the assembly of sister chromatid cohesion. PC formation is also associated with recombination defects leading to reduced numbers of crossovers. Similarly to cohesion mutants, the pairing center protein HIM-8 is mislocalized in akir-1 ;ima-2 double mutants, forming multiple foci. We propose that AKIR-1 and IMA-2 operate in parallel pathways to import and load chromosomally associated cohesin complex proteins in meiotic nuclei, a novel finding for both of these conserved proteins.